Production of Japanese encephalitis virus-like particles using the baculovirus-insect cell system - Hideki Yamaji (2018)
The production of a secreted form of Japanese encephalitis (JE) virus-like particles (VLPs) using the baculovirus-insect cell system was investigated. A recombinant baculovirus that contained the JE virus (JEV) prM signal sequence and the genes encoding the precursor (prM) of the viral membrane protein (M) and the envelope glycoprotein (E) was constructed. Western blotting and enzyme-linked immunosorbent assay (ELISA) of the culture supernatant showed that Spodoptera frugiperda Sf9 cells infected with the recombinant baculovirus had secreted the E protein. Sucrose density-gradient sedimentation analysis of the culture supernatant suggested that secreted E antigen molecules were in a particulate form. Baculovirus-infected Sf9 cells produced more than a 10-fold higher yield of E antigen than that produced by previously reported recombinant CHO cells. Following infection with a recombinant baculovirus encoding a form of prM with a pr/M cleavage site mutation designed to suppre ss cell-fusion activity of E, Sf9 cells showed an E antigen yield comparable to a yield obtained with the baculovirus encoding the authentic form of prM. Baculovirus-infected Trichoplusia ni BTI-TN-5B1-4 (High Five) cells secreted less of the E antigen than Sf9 cells. Moreover, the Drosophila BiP signal sequence gave an E antigen yield comparable to the prM signal sequence, while the honeybee melittin signal sequence and the baculovirus gp64 signal sequence resulted in lower yields of the E antigen. These results provide information important to the development of VLP production processes using the baculovirus-insect cell system. © 2012 The Society for Biotechnology, Japan.